From the Rule of Thumb to the Rule of the Algorithms: Command and Control in Ride-Hailing Platforms - Jeronimo, Rodrigo Constantino [UNESP]; Scorsone, Eric Anthony [UNESP]; Guedes, Sebastião Neto Ribeiro [UNESP] (Taylor & Francis, 2022)
By using a Commonsian approach to the mechanisms of control present in the wealth-creating managerial transactions, we aim to investigate the command-and-control relationship between digital platforms of ride-hailing services and their drivers. Despite being commonly defined as technology companies acting as multisided markets, thus, intermediaries between its end-users, the on-demand ridesharing platforms also share the feature of controlling their labor force—usually working under self-employed statuses—through opaque and unilaterally defined working rules by its algorithms. We argue that, by recovering Commons’ idea of going concerns and their constitutive elements of going plants and going business, platforms can be seen as governance structures whose algorithmic mechanisms have systematized with high detailed capacity the working rules of their services (car rides), substituting the role played by workers’ experience and customs in establishing the methods of work. This transaction between workers and platform results in a state of insecurity on the side of the workers, marked by a lack of democratic participation and asymmetric bargaining power.
Keywords: algorithmic management; Commons; digital platforms; ride-hailing; scientific management